Understanding and Translating Proverbs 25.27: Weighing the "Honorable" Options. Issue 3 (December 2021) - Duke, Rodney K.
Proverbs 25.27, particularly the second verset (27b) as found in the Masoretic Text, has created problems for interpreters. This paper identifies those problems and then lists, summarizes, and evaluates the major options that interpreters have offered as well as offering a couple of new options based on recognizing a double entendre.